Biodegradation of pentachlorophenol (PCP) using indigenous fungal isolates - Ngieng, Ngui Sing (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Pentachlorophenol (PCP) is a man made chemical compound that has been used widely as an effective biocide in agriculture and also in the wood industry. Wide spectrum usage of PCP however has caused uncontrolled release of this toxic compound into the environment. Fungi were therefore isolated from xenobiotic contaminated samples in order to evaluate their potential to be used for degradation of this toxic compound.